1973ネン 12ガツ ニ オケル ヤマト インセキ ノ サイシュウ - 白石, 和行; シライシ, カズユキ; 成瀬, 廉二; ナルセ, レンジ; 楠, 宏; クスノキ, コウ; SHIRAISHI, Kazuyuki; NARUSE, Renji; KUSUNOKI, Kou (国立極地研究所, 1976)
P(論文) 1969年12月,9箇の石質隕石がやまと山脈の南東端付近で発見された(Yamato (a)からYamato (I)と命名).引き続き12箇の石質隕石が1973年12月,第14次南極観測隊の旅行隊によってほぼ同地域で発見された.12箇中,大型のもの4箇(重量500～900 g)はYamato (j), (k), (l), (m)と命名され,Yamato (l)はachondrite,他はchondriteである;残りの8箇(4～40 g)はYamato (n)からYamato (u)と命名された.採集現場での産状写真を示すとともに,地形や氷状についても述べた.将来,さらに発見される可能性があり,やまと山脈南端の限られた裸氷域に隕石が集中している原因や機構の解明のため,将来室内研究と現場での研究の必要なことを述べた. In addition to 9 meteorites, designated as Yamato meteorites, discovered in December 1969 at the SE end of the Yamato Mountains, East Antarctica, 12 stoney meteorites were found in December 1973 in nearly the same area by the traverse glaciology party of the 14th Japanese Antarctic Research Expedition. Eight pieces among 12 were found at the same site as the 1969 collection and the rest were found on the SW side of the Yamato Mountains. Relatively large 4 samples, weighing between 500 and 900 grams, were designated as Yamato (j), (k), (1), and (m), among which Yamato (1) was achondrite and the rest were chondrites; other 8 samples, weighing 4 to 40 grams, were designated as Yamato (n) to (u) in alphabetical order. Geomorphological and glaciological features of the sampling sites are described, suggesting a further extensive search for more meteorites and glaciological research which may account for the concentration of the meteorites. departmental bulletin paper